Analysis of Potential Regional Economic Development in Bengkulu Province in 2022 - Saputro, Redo; Sejati, Martina Ayu (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2024)
Bengkulu Province is one of the developing provinces in Indonesia. The distribution of development and economic growth is still one of the main objectives of development in Indonesia, as well as Bengkulu Province. Development and growth are still centralised in Bengkulu City, causing inequality between regions in Bengkulu Province. This research aims to identify the typology of regions in Bengkulu Province, as an evaluation material for the government in determining priority development areas based on business fields in Bengkulu Province. The research method used is quantitative with sharpened through descriptive analysis. This research uses secondary data sources obtained from BPS Bengkulu Province. Based on the existing business sectors in Bengkulu Province, the primary sector or sectors that still depend on or take advantage of natural conditions, such as; agriculture, forestry and fisheries have the largest contribution to the Bengkulu Province GRDP, which is 27.57%, then the next sector is the Wholesale and Retail Trade sector; Car and Motorcycle Repair, with an average contribution of 15.82%, and the Government Administration sector with a contribution of 8.88%. Data were analysed using Klassen's typology, by dividing or grouping into 4 (four) quadrants based on business field indicators. The results of the Klassen typology analysis in Bengkulu Province based on business fields show that there is close to equity in each sector, typology in quadrants 1, 3, and 4 consists of 5 business fields, while the typology results in quadrant 2, only consists of 2 business fields (Manufacturing, Public Administration & Defence; Compulsory Social Security).Keywords: Regional Typology; Klassen Typology; Economy; Development.